Local Wisdom as a Pillar of Yogyakarta's Community Welfare During Covid-19 - Listyawati, Andayani; Wardani, Raden Roro Ilma Kusuma (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The Covid-19 pandemic became a major test of social resilience for Indonesian society, especially the people of the Special Region of Yogyakarta, as it triggered not only a health crisis but also significant social, economic, and psychological impacts. In this situation, local wisdom emerged as an important form of social capital in strengthening solidarity, social care, and the community’s ability to cope with various social problems. This study aims to describe and illustrate the diversity of local wisdom in the Special Region of Yogyakarta in providing social welfare services for people affected by the Covid-19 pandemic. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation studies involving formal and informal officials as well as community leaders across the five administrative regions of Yogyakarta. The findings show that communities in Yogyakarta City and the four regencies of the Special Region of Yogyakarta continue to preserve and utilize various forms of local wisdom in addressing social problems during the pandemic. These forms of local wisdom include local knowledge in the form of community initiatives and local technology, local culture reflected in traditions, expressions, arts, and social norms, as well as local skills that demonstrate the community’s ability to provide social welfare services. Values such as harmony, social care, mutual cooperation, and helping one another became the main characteristics that strengthened community solidarity, particularly in assisting neighbors affected by Covid-19. This study confirms that local wisdom has strong practical value as a foundation for community social resilience in facing social disasters and humanitarian crises.